PENGARUH WORK-LIFE BALANCE, KEPUASAN KERJA, DAN SUPPORTIVE WORK ENVIRONMENT TERHADAP RETENSI KARYAWAN (Studi Pada Karyawan Tetap PT. Nasmoco Cabang Gombel) - Surya Widiani, Elisabeth Putri; Mas’ud, Fuad (Diponegoro Journal of Management, 2023)
ABSTRACT Employee retention is a process where employees feel driven and motivated to stay in an organization for a long period of time. Employee retention is also defined as a strategy or practice that contributes to keeping employees longer in the organization. Employee retention includes all the activities and practices used by organizations to prevent employees from leaving. Employee retention is considered central to organizational performance. This study aims to analyze the effect of work-life balance, job satisfaction and supportive work environment on employee retention in PT. Nasmoco Gombel Semarang. This study uses primary data through distributing research questionnaires to permanent employees of PT. Nasmoco Gombel Semarang as research samples, and secondary data through journals, books, and relevant data obtained from the company concerned. The data analysis technique used Statistical Program for Social Science with IBM SPSS Statistic 21 application to test the hypothesis and the effect of the relationship between variables. This study involved 63 respondents who were drawn with sensus sampling. The results of this study indicate that work-life balance has no significant effect on employee retention, job satisfaction has a significant effect on employee retention, and supportive work environment has no significant effect on employee retention.